Serotonin Syndrome after Sertraline Overdose in a Child: A Case Report. (19th December 2013) - Grenha, Joana; Garrido, Ana; Brito, Hernani; Oliveira, Maria José; Santos, Fátima
Abstract : Serotonin syndrome is a potentially life-threatening drug effect. It may be misdiagnosed because it has mostly been reported in adults. Case Report . An 8-year-old girl with behavioral problems and medicated with risperidone and sertraline was admitted in the emergency department after she had taken voluntarily 1500 mg of sertraline (50 mg/kg). At admission, she had marked agitation, visual hallucinations, diaphoresis, flushing, and tremor. She had fever and periods of hypertension. She also showed generalized rigidity and involuntary movements. She was treated with fluids and iv diazepam, midazolam, clemastine, and biperiden. As the patient presented a severe insomnia and a progressive rhabdomyolysis, she was transferred to pediatric intensive care unit (ICU), where she was under treatment with cyproheptadine, mechanical ventilation, and muscular paralysis for 11 days. She was discharged from hospital a few days later with no neurological sequelae. Conclusions . Serotonin syndrome is still not well recognized by physicians. In our patient, the diagnosis was made early due to the history of overdose with serotonin reuptake inhibitors and the triad of mental, neurological, and autonomic signs. Parents must be educated to prevent children from having free access to drugs, avoiding self-medication or overdose.